Jewellery Production of the Leningrad Plant of the Russian Gemstones Trust (1946–1957): Models and Technologies - Borovkova, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
Modern researchers are rethinking and revising the works of Soviet industrial art. The article is devoted to the activities of Leningrad Gemstone Processing Plant No. 2 of the Russian Gemstones Trust. The postwar decade saw a rise of the Leningrad jewellery and stonecutting industries. The article is based on a study of the trust’s reference collection, which was acquired for the museum of the Leningrad Mining Institute in 1989. The author studies minutes of artistic councils from 1946 to 1957. Additionally, the research draws upon archival materials and visual and technical data of the former Russian Gemstones exhibition organised at the Mining Museum in 1959–1989. As a result of the study of graphic materials and jewellery of the 1940s and early 1950s, the author identifies references for the development of new jewellery models. The article touches upon the discussion of art projects. Also, it determines the periods of the model range change in the jewellery and stonecutting industries. The study of the documents of the Russian Gemstones Trust and the Leningrad plant of the same name made it possible to identify the names of the artists who created the models of products produced at the trust’s factories. The article focuses on the work of Yu. I. Paas-Alexandrova her capacity as chief artist of the Leningrad Plant No. 2. Models of products designed by Leningrad artists could also be produced at other enterprises. The stamps on jewellery do not always help reliably determine the authorship of the artists of the factory collectives. The data of the Art Councils revealed during the study will further clarify the attribution of jewellery and stone-cutting products of the postwar period and identify the authors of the projects and the dates of their production.